Studi komparasi metode six thinking hats dan metode brainstorming terhadap keterampilan menulis karangan argumentasi ditinjau dari locus of control internal pada peserta didik kelas V sekolah dasar - Saraswati, Ayu Shinta; Slamet, Slamet; Sadiman, Sadiman (Didaktika Dwija Indria, 2019)
Abstract. This research has a purpose to find : (1)the different of argumentative text writing skills between the students that teached by Six Thinking Hats learning method within  Brainstorming learning method ; (2) the different of argumentative text writing skills between the high internal locus of control students and low internal locus of control students, and (3) the interaction between learning method and internal locus of control on the  argumentative text writing skills. Research arranged using quasi experimental research method at 2 x 2 factorial design. The examined population were all the fifth grader students of state elementary school at Laweyan sub district Surakarta in the 2018/2019 academic year. The technique of sampling was using cluster random sampling. The representative sample were Kleco I elementary school and Bratan II elementary school. Data dollected by test and non test technique. The data were analyzed using Two Ways Anava at 5% significance level. This research conclude that (1) there was a different of argumentative text writing skills between the students that teached by Six Thinking Hats learning method within Brainstorming learning method with FA = 11.1345093 > F(0,05;1,62) = 4; (2) there was a different of argumentative text writing skills between the high internal locus of control students and low internal locus of control students with FB= 5.76629985> F(0,05;1,62) = 4; (3) there was no interaction between learning method and internal locus of control on the  argumentative text writing skills with FAB = -0.9813857<F(0,05;1,62) = 4.Keywords : Six Thinking Hats, Brainstorming, Internal Locus of Control, argumentative text writing skills, elementary school